Call interview for early detection and appropriate treatment to decrease COVID-19 pandemic burden - Ghorbani, Fariba; Shafaghi, Shadi; Noorali, Sima; Pourdowlat, Guitti (Researcher Bulletin of Medical Sciences, 2023)
One of the most important concerns during the covid-19 pandemic is an imbalance in health services. Considering significant mortality among hospital staff and the general population, a great apprehension was raised in society. Consequently, many patients with symptoms were rushed to hospitals. In this regard, to keeping clinics away from overcrowding, call interview with patients plays a crucial role in not only patients screening but also treatment approach.